The art of asking in psychotherapy - Marcelo Rodriguez Ceberio; Sonia E. Rodriguez (Interacciones)
Background: the question is an essential instrument of human communication. Not only because the answers introduce information into the systems, but because they constitute a true strategic trigger in psychotherapy. Method: theoretical study. Results and conclusions: the paper explores the art’s theory of asking and the technique of speaking the patient's language as a maneuver that supports the way in which the question is executed. It also tries a typology of questions that were collected in the clinical practice of different therapists. In no way are all the types of questions that were classified, but it is an original work, thought from the systemic paradigm and the strategic systemic model in psychotherapy that makes it possible to systematize numerous questions that are only at the mercy of the creativity and spontaneity of the therapist.